Does China's Trade Expansion Help African Development? - A South-South Trade Model Approach - (:unkn) unknown (My University, 2011)
With the aim to explain the explosive growth of trade between China and Africa, especially the impacts of China's exportation on African countries, a simple South-South trade model is constructed to formulate the idea that for a technologically backward country to improve its production capability, when there exists nontrivial substitution effects, it is better to import from a South country which has superior technology, than from a North country with enormous technological advance. Then the Comtrade panel data are used to assess the impacts of imports from China (in comparison with those from the USA and France) on Sub-Saharan African manufactured exports (as proxies of their production performances). The results confirm the inference drawn from the model.
Keywords: African Research